Od zarządzania marketingowego do zarządzania wiedzą - Śnihur, Janusz (From marketing management to knowledge management, 2006)
Evolution in sphere of management and process of fitting forces necessity of penetration for still market concept changing and instruments of marketing and modern methods of managements. Construction of structure and has fast on purpose models of managements knowledge and complex reconnaissance of expectation of market and preparation of proper offer on this base.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 396-405